Analisis Senyawa Bioaktif Averrhoa bilimbi L. sebagai Penghambat Enzim Siklooksigenase-2 Menggunakan Pendekatan in silico - Mulatsari, Esti; Sumiyati, Yati; Warni, Warni (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Averrhoa bilimbi L. is generally used as a food flavor enhancer and traditional medicine to treat inflammation, cancer sores, cough, fever, gout, rectal bleeding, and hemorrhoids. In vivo and in vitro studies on Averrhoa bilimbi L. have shown anti-inflammatory activity, but the active compounds that play a role in anti-inflammatory activity have not been reported. This study aimed to analyze sixtyfour (64) bioactive compounds in the Averrhoa bilimbi L. plant as cyclooxygenase-2 (COX-2) enzyme inhibitors using in silico approach and predict the pharmacokinetic and toxicological profiles of each compound. The cyclooxygenase-2 enzyme is an enzyme that plays a role in the inflammatory process by converting arachidonic acid into prostaglandin. Increased prostaglandins will cause inflammation. The research method used molecular docking with the application of YASARA, PLANTS, Marvinsketch, Pymol, visualization with PLIP and prediction of ADMET with pkCSM. Control compound used celecoxib. The results showed that there were 13 test compounds that were predicted to have better COX-2 inhibitor activity than celecoxib with good pharmacokinetic properties. Erucic acid has the best pharmacokinetic and toxicity profile. Erucic acid has the potential to be developed as a cyclooxygenase-2 enzyme inhibitor drug.